Upaya Peningkatan Budaya Sadar Bencana Pada Siswa Guna Meningkatkan Kesiapsiagaan SMA Terpadu Baitul Hikmah Depok - Rahmat, Hayatul Khairul; Hiram, Taqwa Putra Budi Purnomo Sidi; Alamsyah, Achmad Nurfikri; Bimantara, M. Aji (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
Disaster preparedness is closely related to the level of public awareness in facing disasters or also known as disaster awareness culture. Therefore, schools have an important role in providing adequate provisions for their students through disaster education in facing the challenges of existing potential disaster threats which are part of school preparedness. One effort to improve the culture of disaster awareness can be done through education so that learning activities are expected to run optimally and with quality in accordance with learning objectives in the context of disaster mitigation. Meanwhile, disaster mitigation has meaning as a form of protection effort before, during and after a disaster occurs. Overall, disaster mitigation education can be carried out with disaster literacy. Disaster literacy is an individual's capacity to read, understand and use disaster information. Disaster literacy in question is disaster mitigation carried out in schools. Baitul Hikmah Depok Integrated High School which is located at Kp. Waterfall No. 90, RT. 02/ RW. 02, Curug Village, District. Bojongsari, Depok City, 16517 is a school that experienced the impact of the flood disaster in March 2023. Based on observations around Baitul Hikmah Depok Integrated High School, poor sanitation, minimal water absorption, and fairly high rain intensity caused the school to be flooded. . Based on the above, it is important to carry out community service activities entitled "Efforts to Increase Disaster Awareness Culture among Students to Improve Preparedness at Baitul Hikmah Depok Integrated High School". The output target of this community service activity is to convey knowledge about the introduction of disaster awareness culture and provide material for making digital posters regarding disaster awareness culture in schools. After carrying out community service activities, there is a conclusion that this community service activity has been carried out communicatively, as seen from the enthusiastic participants in the question and answer process, responding when asked questions and listening to explanations of the questions given. With this training, students can understand the steps that can be taken to mitigate floods in order to increase flood disaster preparedness for students at Baitul Hikmah Depok Integrated High School.